1996
DOI: 10.1038/nsb0996-747
|View full text |Cite
|
Sign up to set email alerts
|

The hairpin stack fold, a novel protein architecture for a new family of protein growth factors

Abstract: The granulin/epithelin protein motif has an unusual structure consisting of a parallel stack of beta-hairpins stapled together by six disulphide bonds. The new structure also contains a folding subdomain shared by small toxins, protease inhibitors as well as the EGF-like protein modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
172
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(178 citation statements)
references
References 27 publications
4
172
0
2
Order By: Relevance
“…Two-dimensional nuclear magnetic resonance analysis of purified carp GRN-1 revealed that the peptide backbone adopts a unique conformation of a parallel stack of beta-hairpins in the form of a left-handed helix. (3) Recombinant mammalian GRN modules show a similar, but less rigid structure (4) (Fig. 1B).…”
Section: Introductionmentioning
confidence: 98%
“…Two-dimensional nuclear magnetic resonance analysis of purified carp GRN-1 revealed that the peptide backbone adopts a unique conformation of a parallel stack of beta-hairpins in the form of a left-handed helix. (3) Recombinant mammalian GRN modules show a similar, but less rigid structure (4) (Fig. 1B).…”
Section: Introductionmentioning
confidence: 98%
“…GrnA to F contain 12 highly conserved cysteine (Cys) residues (Fig. 1) Plowman et al, 1992] and are folded in four stacked b-hairpins twisted around an axial rod of disulfide bridges [Hrabal et al, 1996]. GrnG contains only 10 Cys residues Plowman et al, 1992] but it was suggested that the lack of two Cys residues remains compatible with a stacked b-hairpin fold [Hrabal et al, 1996].…”
Section: Grn Protein and Genementioning
confidence: 99%
“…The larger precursor is known by several names, including granulin/epithelin precursor (8), proepithelin (9), acrogranin (10), PC cell-derived growth factor (PCDGF) (11), and progranulin. Granulins have a unique 12-cysteine motif that is arranged in four ␤-hairpins, stacked one upon another in a helical formation and connected via a central rod of disulfide bonds (12)(13)(14). Structurally, granulins are distinct from most growth factors, with the exception of the epidermal growth factor/transforming growth factor-␣ family (13).…”
mentioning
confidence: 99%
“…Granulins have a unique 12-cysteine motif that is arranged in four ␤-hairpins, stacked one upon another in a helical formation and connected via a central rod of disulfide bonds (12)(13)(14). Structurally, granulins are distinct from most growth factors, with the exception of the epidermal growth factor/transforming growth factor-␣ family (13). In addition to the mammalian granulins of human (1,6), rat (2,12), mouse (10,15), and horse (16), granulin-like proteins have been identified in a number of non-mammalian organisms including the nematode Caenorhabditis elegans (17), the locust (18), the mussel (19), the marine worm Hediste diversicolor (20), and teleosts (bony fish) (21)(22)(23).…”
mentioning
confidence: 99%